Genetic Analysis Of Grain Yield And Related Traits In Sorghum (Sorghum Bicolor (L.) Moench) Under Phosphorus Deficient Field Conditions In Southern Mali - Chiaka, D. (University Of Ghana, 2017)
Sorghum (Sorghum bicolor (L) Moench), the fifth most important cereal in the world is a multipurpose crop that plays a crucial role in human diets. Sorghum grain yield is heavily constrained by low phosphorus levels that limit its availability for plant use. Genetic improvement approaches that combine high grain yields with tolerance to low phosphorus levels would greatly improve adoption of such sorghum varieties. High grain yield reduction as a results of low soil phosphorus levels have been reported in Mali and they form the primary focus of this study. Determination of farmer preferences for grain and panicle traits in sorghum was undertaken to understand farmer preferred traits in addition to high yield. Genomic segments responsible for grain quality, panicle traits and other yield related traits under high and low phosphorus levels were identified. Alternative selection strategies targeting grain yield improvement under both high and low phosphorus levels (P-deficient) field conditions were also explored. The influence of environment on sorghum 1083 BC1F5 BC-NAM progenies for grain yield were elucidated. Results from focus group discussions with farmers at Sibi and Dioila clearly indicated that in addition to high grain yield, there were high preferences for grain-hardened open panicles with good threshability. Early maturing sorghum varieties were also much preferred especially under semi-arid conditions. A high genetic correlation (rG = 0.81) for grain yield was detected under HP and LP condition. The direct selection for grain yield was predicted to be 13% more efficient than the indirect selection. Using a nested mapping approach, a total of 84 QTLs detected by both bi-parental and Association mapping approaches were found to define the genetic architecture of tolerance to low and high phosphorus levels in sorghum. Field evaluations of a set of 13 backcross nested association mapping (BC-NAM) populations was done under contrasting P levels. A multi-environment University of Ghana http://ugspace.ug.edu.gh iii evaluation of 298 sorghum lines for grain yield indicated that non-additive genetic variance was more important across years under contrasting phosphorus levels. The findings from this study will contribute to the improvement of knowledge about farmers’ sorghum preferred traits and genetic control of those traits LP field conditions culminating in genetic improvement of the crop and better adoption of new varieties by farmers.
Keywords: Sorghum Bicolor L. Moench; Grain Yield; cereal